The effect of propylene glycol and polyethylene glycol 400 on physicochemical properties of peel off mask of nanosilver using bioreductor Sweet Orange Peels (Citrus sinensis L. Osbeck) - Dian Eka Ermawati; Fridha Angelina Pamuji; Adi Yugatama (Universitas Ahmad Dahlan, 2021)
Nanosilver (AgNPs) can be synthesized using plant extracts that safe, simple, and environmentally friendly. Sweet orange contains flavonoids and citric acid, which can be a bioreductor and capping agent in silver biosynthesis to increase antimicrobial activity. AgNPs are then dispersed in a gel for acne treatment through a peel-off mask preparation. Humectants provide moisture, prevent skin irritation and regulate the viscosity of the preparation. Propylene Glycol (PG) and Polyethylene Glycol 400 (PEG 400) are humectants combined to obtain good physicochemical properties of the preparation. This study aims to determine the character of AgNPs and the effect of humectant combinations on the physicochemical properties of peel-off mask preparations. AgNPs characterization was performed using UV-VIS Spectrophotometry, Particle Size Analysis, and Scanning Electron Microscope. The PG-PEG 400 combinations are F1 (0: 100%); F2 (25%: 75%); F3 (50%: 50%); F4 (75%: 25%) and F5 (100%: 0). The physical-chemical test for 28 days included organoleptic, viscosity, dry time, and pH. The biosynthesis results produced AgNPs with maximum absorption of nanoparticles at 435 nm, rod morphological shapes measuring 106 Â± 10.6 nm, and PI 0.26 Â± 0.06. Statistical analysis showed that the PG-PEG 400 combination significantly affected the viscosity, dispersibility, and dry time of the preparation but affected nothing to pH. The combination of PG-PEG 400 decreased the viscosity and increased the dispersibility of peel-off mask preparation. The higher concentration of propylene glycol caused the dry time of preparation to become longer. Formulas with PG-PEG 400 combination of 25%: 75% and 75%: 25% meet the requirements of viscosity, dispersibility, dry time, and pH and not significant changes during 28 days of storage at room temperature.